Two-Degrees-of-Freedom Lateral Vehicle Control using Nonlinear Model Based Disturbance Compensation. Issue 11 (2016) - Hahn, Stefan; Zindler, Klaus; Jumar, Ulrich
Abstract: Evasive pedestrian protection systems avoid imminent collisions with vulnerable road users via autonomous evasive maneuvers. For this purpose, a new lateral control scheme is presented in this paper. We propose a new two-degrees-of-freedom control structure consisting of a linear PDT2 controller and a nonlinear model based disturbance compensation. By means of the latter component the highly nonlinear influence of the evasive trajectory's curvature (disturbance variable) to the lateral deviation (controlled variable) is compensated. In contrast to classical nonlinear control methods, the proposed control scheme does not require the measurement of the complete state vector.